Proteomic Characterization of Two Extracellular Vesicle Subtypes Isolated from Human Glioblastoma Stem Cell Secretome by Sequential Centrifugal Ultrafiltration - Fabrizio Di Giuseppe; Marzia Carluccio; Mariachiara Zuccarini; Patricia Giuliani; Lucia Ricci-Vitiani; Roberto Pallini; Paolo De Sanctis; Roberta Di Pietro; Renata Ciccarelli; Stefania Angelucci (Biomedicines, 2021)
Extracellular vesicles (EVs) released from tumor cells are actively investigated, since molecules therein contained and likely transferred to neighboring cells, supplying them with oncogenic information/functions, may represent cancer biomarkers and/or druggable targets. Here, we characterized by a proteomic point of view two EV subtypes isolated by sequential centrifugal ultrafiltration technique from culture medium of glioblastoma (GBM)-derived stem-like cells (GSCs) obtained from surgical specimens of human GBM, the most aggressive and lethal primary brain tumor. Electron microscopy and western blot analysis distinguished them into microvesicles (MVs) and exosomes (Exos). Two-dimensional electrophoresis followed by MALDI TOF analysis allowed us to identify, besides a common pool, sets of proteins specific for each EV subtypes with peculiar differences in their molecular/biological functions. Such a diversity was confirmed by identification of some top proteins selected in MVs and Exos. They were mainly chaperone or metabolic enzymes in MVs, whereas, in Exos, molecules are involved in cell–matrix adhesion, cell migration/aggressiveness, and chemotherapy resistance. These proteins, identified by EVs from primary GSCs and not GBM cell lines, could be regarded as new possible prognostic markers/druggable targets of the human tumor, although data need to be confirmed in EVs isolated from a greater GSC number.